2002
DOI: 10.1093/oxfordjournals.molbev.a004133
|View full text |Cite
|
Sign up to set email alerts
|

An Insect Molecular Clock Dates the Origin of the Insects and Accords with Palaeontological and Biogeographic Landmarks

Abstract: A unified understanding of >390 Myr of insect evolution requires insight into their origin. Molecular clocks are widely applied for evolutionary dating, but clocks for the class Insecta have remained elusive. We now define a robust nucleotide and amino acid mitochondrial molecular clock encompassing five insect orders, including the Blattaria (cockroaches), Orthoptera (crickets and locusts), Hemiptera (true bugs), Diptera, and Lepidoptera (butterflies and moths). Calibration of the clock using one of the earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
311
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(325 citation statements)
references
References 50 publications
11
311
1
2
Order By: Relevance
“…Whereas the diversification of the Yucca crown group began 6.41-10.19 Myr ago, previous estimates indicate that yucca moths began to diversify ca 40G11.1 Myr (ago; Pellmyr & Leebens-Mack 1999). Although the age estimates for the pollinating moths have recently been revised downwards to 32 Myr (Gaunt & Miles 2002), these are still several million years prior to our very oldest estimates for the common ancestor yuccas and are tens of millions of years older than the maximum-likelihood estimate.…”
Section: Discussionmentioning
confidence: 61%
“…Whereas the diversification of the Yucca crown group began 6.41-10.19 Myr ago, previous estimates indicate that yucca moths began to diversify ca 40G11.1 Myr (ago; Pellmyr & Leebens-Mack 1999). Although the age estimates for the pollinating moths have recently been revised downwards to 32 Myr (Gaunt & Miles 2002), these are still several million years prior to our very oldest estimates for the common ancestor yuccas and are tens of millions of years older than the maximum-likelihood estimate.…”
Section: Discussionmentioning
confidence: 61%
“…3). The C. elegans fat-like-related molecules, Cdh-3 and Cdh-4, are poorly clustered suggesting that the onset of development of modern Fat cadherins may have occurred about 430 million years ago when insects emerged (29).…”
Section: Silencing Of Fat-like Transcript Impairs Tubular Tissue Formmentioning
confidence: 99%
“…Such conservation was shown by the ability of the Anopheles gambiae ortholog of fru to function when ectopically expressed in D. melanogaster resulting in the production of the fru-dependent male-specific muscle of Lawrence (Gailey et al, 2006). As A. gambiae and D. melanogaster have been separated for B250 mya (Gaunt and Miles, 2002;Zdobnov et al, 2002), Gailey et al (2006) concluded that fru has been functionally conserved across this time period. This has been further emphasised with the finding that RNAi-mediated knockdown of fru extinguishes male courtship in the cockroach Blattella germanica, suggesting that the large role fru has in the production of male sexual behaviours has been conserved for at least a large portion of insect evolution (Clynen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%